Can Companies Providing Public Sanitation Services Commercialize Treated Wastewater? - Monteza Palacios, Carlos (2015)
The authors of this article conducted an analysis of the companies providing publicsanitation services. In particular, they focus on determining if these are legally entitled to market the treated waste water generated as a result of the provision of public services in charge. Additionally, in order to provide a complete analysis of the issue, the authors speak about the powers of the National Water Authority and his power to permit reuse of treated wastewater.